Scientific opinion on the safety of monacolins in red yeast rice - EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS); Maged Younes; Peter Aggett; Fernando Aguilar; Riccardo Crebelli; Birgit Dusemund; Metka Filipič; Maria Jose Frutos; Pierre Galtier; David Gott; Ursula Gundert‐Remy; Gunter Georg Kuhnle; et al. (EFSA Journal, 2018)
Abstract The Panel on Food Additives and Nutrient Sources added to Food (ANS) was asked to deliver a scientific opinion on the safety of monacolins in red yeast rice (RYR) and to provide advice on a dietary intake of monacolins that does not give rise to concerns about harmful effects to health. The Panel reviewed the scientific evidences available as well as the information provided by interested parties in response of a public ‘Call for data’ launched by EFSA. The Panel considered that monacolin K in lactone form is identical to lovastatin, the active ingredient of several medicinal products authorised for the treatment of hypercholesterolaemia in the EU. On the basis of the information available, the Panel concluded that intake of monacolins from RYR via food supplements, could lead to estimated exposure to monacolin K within the range of the therapeutic doses of lovastatin. The Panel considered that the available information on the adverse effects reported in humans were judged to be sufficient to conclude that monacolins from RYR when used as food supplements were of significant safety concern at the use level of 10 mg/day. The Panel further considered that individual cases of severe adverse reactions have been reported for monacolins from RYR at intake levels as low as 3 mg/day. The Panel concluded that exposure to monacolin K from RYR could lead to severe adverse effects on musculoskeletal system, including rhabdomyolysis, and on the liver. In the reported cases, the product contained other ingredients in addition to RYR. However, these reported effects in particular musculoskeletal effects, have both occurred after ingestion of monacolin K and lovastatin independently. On the basis of the information available and several uncertainties highlighted in this opinion, the Panel was unable to identify a dietary intake of monacolins from RYR that does not give rise to concerns about harmful effects to health, for the general population, and as appropriate, for vulnerable subgroups of the population.